Prevalence of depression in servers of the National Institute of Social Security - Missiatto, Leandro Aparecido Fonseca; Feitosa, Fabio Biasotto; Rodríguez, Tomás Daniel Menéndez; Mathis, Maria Alice Simões de (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2019)
This study deals with a survey conducted with 132 government employee of the National Institute of Social Security of the State of Rondônia, whose objective was to verify the prevalence of depression in this sample. A socioeconomic questionnaire developed by the researchers and the Patient Health Questionnaire-9 was used as instruments. The results show that the prevalence of depression in this group was higher in the government employee of the interior of the State, with high schooling and who are still studying. This information can contribute to the elaboration of specific mental health policies for the context of the INSS / RO employees.